2011
DOI: 10.1017/s0022029911000537
|View full text |Cite
|
Sign up to set email alerts
|

Age-related decline in macrophage and lymphocyte functions in mice and its alleviation by treatment with probiotic Dahi containingLactobacillus acidophilusandBifidobacterium bifidum

Abstract: This study evaluated the effects of probiotic Dahi administration in ageing mice on macrophage and lymphocyte functions. Probiotic Dahi were prepared by co-culturing in buffalo milk (3% fat) Dahi bacteria (Lactococcus lactis ssp. cremoris NCDC-86 and Lc. lactis ssp. lactis biovar diacetylactis NCDC-60) along with Lactobacillus acidophilus LaVK2 (La-Dahi) or combined Lb. acidophilus and Bifidobacterium bifidum BbVK3 (LaBb-Dahi). Four groups of 12 mo old mice were fed for four months, with the supplements (5 g/d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Studies from our laboratory have shown that this probiotic Dahi attenuates dimethylhydrazine‐induced gastrointestinal carcinogenesis; diminishes diet induced hypercholesteraemia and atherogenic index in rats; stimulates the macrophage activity and confers protection against enteric infection in mice . This probiotic Dahi also reverses the age‐related decline in tissue antioxidant activities and improves expression of biomarkers of ageing, peroxisome proliferators activated receptors‐α (PPAR‐α), senescence marker protein‐30 (SMP‐30) and klotho (maintains calcium and phosphorus homeostasis) in hepatic and kidney tissues and alleviates macrophages and lymphocyte functioning in aged mice . In addition, the same product has been reported to have an anti‐colitis effect and it modulates the formation of aberrant crypt foci, mucin‐depleted foci and cell proliferation on 1,2‐dimethylhydrazine‐induced colorectal carcinogenesis in Wistar rats …”
Section: Introductionmentioning
confidence: 99%
“…Studies from our laboratory have shown that this probiotic Dahi attenuates dimethylhydrazine‐induced gastrointestinal carcinogenesis; diminishes diet induced hypercholesteraemia and atherogenic index in rats; stimulates the macrophage activity and confers protection against enteric infection in mice . This probiotic Dahi also reverses the age‐related decline in tissue antioxidant activities and improves expression of biomarkers of ageing, peroxisome proliferators activated receptors‐α (PPAR‐α), senescence marker protein‐30 (SMP‐30) and klotho (maintains calcium and phosphorus homeostasis) in hepatic and kidney tissues and alleviates macrophages and lymphocyte functioning in aged mice . In addition, the same product has been reported to have an anti‐colitis effect and it modulates the formation of aberrant crypt foci, mucin‐depleted foci and cell proliferation on 1,2‐dimethylhydrazine‐induced colorectal carcinogenesis in Wistar rats …”
Section: Introductionmentioning
confidence: 99%
“…Thus, for example, they increased the response of specific antibodies against infection [17,18]. Nevertheless, there are also several articles showing the positive effects of probiotics on old experimental animals [19,37,38].…”
Section: Discussionmentioning
confidence: 99%
“…101 Similarly, probiotic dahi intake for four months improved the phagocytosis and cytokine release in murine macrophages and improved the lymphocyte in vitro proliferative capacity. 102 Furthermore, Meyer et al (2007) assessed the effects of fermented dairy beverage ingestion over four weeks, and demonstrated upregulated pro-inflammatory cytokines, i.e. IL-1β and TNF-α and IFN-γ, in the peripheral blood of healthy young women.…”
Section: Probiotics Act As a Promising Modulator In Host Cytokine Res...mentioning
confidence: 99%